Comparison of traditional and modern methods for identification of economically important wireworm species (Coleoptera: Elateridae) - Eva PRAPROTNIK; Jaka RAZINGER; Stanislav TRDAN (Acta Agriculturae Slovenica)
Wireworms are larvae of click beetles (Coleoptera: Elateridae) and are well known pests of economic importance. Knowing the species diversity in a particular area is important, as the ecological requirements and consequent management strategies of individual species vary. Morphological identification of wireworms is challenging; separating between individual species is often almost impossible. Molecular methods therefore complement morphological methods. Mitochondrial gene for cytochrome oxidase I is most commonly used for molecular identification of wireworms. In this study we list molecular, morphological and behavioural methods for wireworm identification and also highlight the advantages and disadvantages of these methods. At the end of the article, a simplified morphological identification key for determining economically important wireworm species of the genus Agriotes in Slovenian language is attached.